Orthorhombic phase stabilization and transformation phase process in zirconia tantalum-doped powders and spark plasma sintering systems. Issue 10 (August 2017) - Sponchia, G.; Boffelli, M.; Back, M.; Zhu, W.; Domínguez Rodríguez, A.; Pezzotti, G.; De Portu, G.; Riello, P.; Benedetti, A.
Abstract: The role of different amount (from 1 to 20 mol%) of tantalum Ta(V) into the zirconia lattice has been investigated in different powders systems prepared via co-precipitation and after calcination. The X-ray diffraction and Raman analyses, have confirmed the presence of an orthorhombic phase in all the samples. The stability of this phase has been investigated by "in situ" X-ray diffraction analysis from 100 °C to 1000 °C and after the subsequent cooling. A phase transformation mechanism, with the formation of a poor (monoclinic) and a rich phase (orthorhombic) in Ta has been consider in order to explain the XRD patterns obtained at different temperatures. The characterization of the orthorhombic phase on bulk ceramic specimens prepared via Spark Plasma Sintering (SPS) has been also investigated. SEM analysis has confirmed the presence of a two-phase system.